Mean Apparent Propagator MRI Is Better Than Conventional Diffusion Tensor Imaging for the Evaluation of Parkinson’s Disease: A Prospective Pilot Study - Le, Hongbo; Zeng, Weike; Zhang, Huihong; Li, Jianing; Wu, Xiaoyan; Xie, Mingwei; Yan, Xu; Zhou, Minxiong; Zhang, Huiting; Wang, Mengzhu; Hong, Guobin; Shen, Jun (Frontiers in Aging Neuroscience, 2020)
Background and Purpose: Mean apparent propagator (MAP) MRI is a novel diffusion imaging method to map tissue microstructure. The purpose of this study was to evaluate the diagnostic value of the MAP MRI in Parkinson's disease (PD) in comparison with conventional diffusion tensor imaging (DTI). Method: 23 PD patients and 22 age- and gender-matched healthy controls were included. MAP MRI and DTI were performed on a 3T MR scanner with a 20-channel head coil. The MAP metrics including mean square displacement (MSD), return to the origin probability (RTOP), return to the axis probability (RTAP) and return to the plane probability (RTPP), and DTI metrics including fractional anisotropy (FA) and mean diffusivity (MD), were measured in subcortical gray matter and compared between the two groups. The receiver operating characteristic (ROC) curve was used to analyze the diagnostic performance of all the metrics. The association between the diffusion metrics and disease severity was assessed by Pearson correlation coefficient analysis. Results: For MAP MRI, the mean values of MSD in the bilateral caudate, pallidum, putamen, thalamus and substantia nigra (SN) were higher in PD patients than in healthy controls (pFDR ≤ 0.001); the mean values of the zero displacement probabilities (RTOP, RTAP and RTPP) in the bilateral caudate, pallidum, putamen and thalamus were lower in PD patients (pFDR < 0.001). For DTI, only FA in the bilateral SN was significantly higher in PD patients than those in the controls (pFDR < 0.001). ROC analysis showed that the areas under the curves of MAP MRI metrics (MSD, RTOP, RTAP and RTPP) in the bilateral caudate, pallidum, putamen and thalamus (range, 0.85-0.94) were greater than those of FA and MD of DTI (range, 0.55-0.69) in discriminating between PD patients and healthy controls. RTAP in the ipsilateral pallidum (r = -0.56, pFDR = 0.027), RTOP in the bilateral and contralateral putamen (r = -0.58, pFDR = 0.019; r = -0.57, pFDR = 0.024) were negatively correlated with UPDRS Ⅲ motor scores.